2022
DOI: 10.1055/s-0042-1748889
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Cardiovascular Death after Venous Thromboembolism: Results from a Prospective Cohort Study

Abstract: Background Cardiovascular deaths (CVDTs) are more frequent in patients with venous thromboembolism (VTE) than in the general population; however, risk factors associated with this increased risk of CVDT in patients with VTE are not described. Methods To determine the risk factors of CVDT in patients with VTE from a multicenter prospective cohort study, Fine and Gray subdistribution hazard models were conducted. Results Of the 3,988 included patients, 426 (10.7%) died of CVDT during a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. 2 3 4 5 6 7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. 2 3 4 5 6 7…”
mentioning
confidence: 99%
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. [2][3][4][5][6][7] Pregnancy is an important risk factor for VTE. Several previous studies reported the incidence of pregnancy-associated VTE (PA-VTE) for Western population.…”
mentioning
confidence: 99%
“…[2][3][4] Indeed, potential risk factors for recurrence of venous thromboembolism have been investigated, 5,6 and some conditions may be predisposing to the high long-term risk of cardiovascular events in this population. 7 Anticoagulant treatment is effective in reducing recurrent venous thromboembolism by over 90%, but it is associated with the risk for life-threatening and even fatal bleeding complications. 8 Indeed, the perceived risk of bleeding limits every-day life activities in a substantial proportion of patients during anticoagulant treatment.…”
mentioning
confidence: 99%
“…2 3 4 Indeed, potential risk factors for recurrence of venous thromboembolism have been investigated, 5 6 and some conditions may be predisposing to the high long-term risk of cardiovascular events in this population. 7…”
mentioning
confidence: 99%
“…As in other fields of research on VTE, it should be interesting to combine clinical items (including family history), genetic factors, and biomarkers to try to outline the profile of patients at particularly high risk of incident VTE and VTE-related complications, given the intense interest into this area of risk profiling. [12][13][14][15][16][17][18][19][20][21] Hence, these could be applied to each woman approaching ART and validate scores that can be helpful in identifying those individuals at higher risk.…”
mentioning
confidence: 99%